Layered double hydroxide based active corrosion protective sealing of plasma electrolytic oxidation/sol-gel composite coating on AA2024 - Bouali, A.C. (2019)
This work reports a novel approach for growing layered double hydroxide (LDH) films on any plasma electrolytic oxidation (PEO) coated AA2024 independently of the nature of the PEO coating. The specific PEO coating chosen to carry out this work is considered to be not suitable for direct LDH growth because of phase composition and morphological features. In this paper, we describe a new methodology that consists of covering the PEO coating with a thin layer of aluminum oxide based xerogel as the source of aluminate ions for subsequent in-situ LDH growth. X-ray diffraction (XRD) and scanning electron microscope (SEM) images showed a successful formation of LDHs on the surface. An improvement in terms of active corrosion protection was also demonstrated by electrochemical impedance spectroscopy (EIS) and scanning vibrating electrode technique (SVET).